2018
DOI: 10.1155/2018/6870645
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Solvent Environment on the Optical Behavior of Chemically Synthesized Silicon Nanoparticles

Abstract: Silicon nanoparticles (Si-NPs) were prepared by solution-based chemical etching method. Optical characteristics of the as-prepared Si-NPs were investigated in different polar and nonpolar organic solvents. The emission and absorption properties of Si-NPs were tuned by altering the environment (solvents). The variation in absorption coefficient was observed because of the solvent interaction nature of Si-NPs. Si-NPs in polar aprotic and nonpolar solvents manifested good luminescence under UV excitation. PL inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This discrepancy in the PL peak position is attributed to the variation of the dielectric environment, where the PL peak energy tends to decrease in the solid form compared to the polar solvent. 43,44 To the best of our knowledge, this is the first report of PL emission and the spectra of solid dispersed MQDs. Our developed Ti 2 N MQDs can be excited and emitted in the form of a thin film with a wide range of excitation wavelengths.…”
Section: Resultsmentioning
confidence: 80%
“…This discrepancy in the PL peak position is attributed to the variation of the dielectric environment, where the PL peak energy tends to decrease in the solid form compared to the polar solvent. 43,44 To the best of our knowledge, this is the first report of PL emission and the spectra of solid dispersed MQDs. Our developed Ti 2 N MQDs can be excited and emitted in the form of a thin film with a wide range of excitation wavelengths.…”
Section: Resultsmentioning
confidence: 80%
“…It has been widely reported that the solvent environment will affect the optical behavior of multiple synthetic products during the chemical synthetic process. As an example, acetone or propanone (chemical formula CH 3 COCH 3 ) serves as an important organic solvent in its own right, in industry, at home, and in the laboratory. Many articles have reported the refractive indices of acetone when used as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…It occurs because both emissions and relaxation decay lie in the short‐wavelength side of the spectrum to longer wavelengths. The emission at a longer wavelength requires that the fluorophores relax before emission, and thus it is delayed by relaxation time 47‐50 …”
Section: Resultsmentioning
confidence: 99%
“…The lower values are due to higher defect density, poor absorption of light, and low photo‐generation excitons. The density of defects has a significant impact on V OC and thus PCE 49,51 . In general, with an increase in defect density, the V OC decreases while the J SC may or may not be influenced by the density of defects 52,53 .…”
Section: Device Fabrication and Characterisationmentioning
confidence: 99%